(untitled) (Balneo and PRM Research Journal, 2024)
Proximal humerus fracture ranks third in the elderly after femoral neck fractures and distal radius fractures, and seventh in adults, and the risk of occurrence is related to advancing age. In this study we aimed to analyze the efficacy of a 24-weeks physical therapy programme based on a particular methodology consisting of the reprogramming of the specific proprioceptive neuromuscular facil-itation techniques added to the classical physical therapy and by introducing modern interactive therapies and technologies: Capacitive Resistive Electric Transference, Instrument Assisted Soft Tissue Mobilization, kinesiological tapes and PRAMA system, compared with classical physical therapy. Our study included 26 patients, aged between 18 and 55 years, with proximal humerus fracture, who complete the 24-weeks rehabilitation programme. We assessed pain, shoulder range of motion, muscle strength and the ability to perform activities of daily living. The statistical analysis was performed using IBM SPSS and Excel 2021. The results showed statistically significant im-provement in all shoulder motion, increased muscle strength, decreased pain, and a better ability to perform daily activities. The physical therapy programme based on the proposed particular methodology has proven to be more effective than classical physical therapy, both regarding the improvement of the movement parameters compared to the physiological values, as well as the symmetry of both shoulders.